Facility management in Qatar: current state, perceptions and recommendations. Issue 5 (4th April 2017) - Rybkowski, Zofia K.; Shepley, Mardelle M.; Bryant, John A.; Skelhorn, Cynthia; Amato, Alex; Kalantari, Saleh
Abstract : Purpose: This paper aims to identify the current challenges and opportunities faced by the facility managers (FMs) in Doha, Qatar. Design/methodology/approach: Researchers queried 40 FMs about their experience working in Qatar, using interviews and workshops. Findings: Comments gathered followed general patterns. Participants expressed appreciation for their work, but also concern about cultural challenges they faced managing facilities in the region. In general, it was agreed that the low cost of water and energy in Qatar is one of the largest obstacles to conserving resources; however, current consumption is not sustainable. Research limitations/implications: The sensitive nature of this study made strict demands on the research team to maintain participant anonymity during data collection and reporting. This sensitivity also limited the sample size; a larger sample size for future research would support greater generalizability. Social implications: Qatar is taking steps to reduce its per capita carbon footprint and energy use, which is among the highest in the world. However, there appears to be a disconnect between Qatar's expressed intentions and its actions with respect to facility management. To ensure that Qatar manages resources more efficiently, participants recommended that reduced energy use standards be adopted and legally mandated. This action would address many of the challenges, incentivize increased qualifications and training of FM professionals working in Qatar and encourage improvement of the long-term performance of buildings which are energy drains and heavy contributors to greenhouse gas emissions. Originality/value: Prior to this study, little has been published about current practices of facility management in Doha, Qatar, and the challenges and opportunities that FMs face in this region.